Association Between Early Idiopathic Neonatal Jaundice and Urinary Tract Infections. (24th March 2017) - Özcan, Murat; Sarici, S Ümit; Yurdugül, Yüksel; Akpinar, Melis; Altun, Demet; Özcan, Begüm; Serdar, Muhittin A; Sarici, Dilek
Background and purpose: Etiologic role, incidence, demographic, and response-to-treatment characteristics of urinary tract infection (UTI) among neonates, its relationship with significant neonatal hyperbilirubinemia, and abnormalities of the urinary system were studied in a prospective investigation in early (≤10 days) idiopathic neonatal jaundice in which all other etiologic factors of neonatal hyperbilirubinemia were ruled out. Patients and methods: Urine samples for microscopic and bacteriologic examination were obtained with bladder catheterization from 155 newborns with early neonatal jaundice. Newborns with a negative urine culture and with a positive urine culture were defined as group I and group II, respectively, and the 2 groups were compared with each other. Results: The incidence of UTI in whole of the study group was 16.7%. Serum total and direct bilirubin levels were statistically significantly higher in group II when compared with group I ( P = .005 and P = .001, respectively). Decrease in serum total bilirubin level at the 24th hour of phototherapy was statistically significantly higher in group I compared with group II ( P = .022). Conclusions: Urinary tract infection should be investigated in the etiologic evaluation of newborns with significant hyperbilirubinemia. The possibility of UTI should be considered in jaundiced newborns who do not respond to phototherapy well or have a prolonged duration of phototherapy treatment.